The Role of Leptin in the Development of Energy Homeostatic Systems and the Maintenance of Body Weight - LeDuc, Charles A.; Skowronski, Alicja A.; Rosenbaum, Michael (Frontiers in Physiology, 2021)
LEP is a pleiotropic gene and the actions of leptin extend well beyond simply acting as the signal of the size of adipose tissue stores originally proposed. This is a discussion of the multi-system interactions of leptin with the development of the neural systems regulating energy stores, and the subsequent maintenance of energy stores throughout the lifespan. The prenatal, early postnatal, and later postnatal effects of leptin on systems regulating body energy stores and on the energy stores themselves are heavily influenced by the nutritional environment which leptin exposure occurs. This review discusses the prenatal and early postnatal (sometimes called “perinatal”) roles of leptin in establishing the neuronal circuitry and other systems relevant to the adiposity set-point (or “threshold”) and the role of leptin in maintaining weight homeostasis in adulthood. Therapeutic manipulation of the intrauterine environment, use of leptin sensitizing agents, and identification of specific cohorts who may be more responsive to leptin or other means of activating the leptin signaling pathway are ripe areas for future research.